Entrepreneurial Orientation, Agility, and Sustainable Performance in Indonesian SMEs - Justin Wijaya; Denny Bernardus Kurnia Wahyudono; Christian Herdinata (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Small and Medium Enterprises (SMEs) are vital contributors to economic development, employment generation, and innovation. However, SMEs in Indonesia face escalating sustainability challenges driven by digital transformation, shifting consumer behavior, and intensifying global competition, necessitating an examination of the strategic capabilities that underpin long-term sustainable performance. Objective: This research examines how Entrepreneurial Orientation (EO), as the independent variable, affects sustainable business performance and investigates the role of pro-growth entrepreneurial agility as the mediating variable in the EO–SBP relationship among Indonesian SMEs. Methods: This research uses a quantitative approach and applies PLS-SEM to analyze data collected from 300 SME owners across different business sectors. Before testing the proposed model, the reliability and validity of the measurement instruments were carefully evaluated. Results: The results reveal that entrepreneurial orientation has a positive impact on sustainable business performance and entrepreneurial agility. This confirms the fully developed mediating role of entrepreneurial agility and suggests that SMEs need to develop both an entrepreneurial mindset and dynamic capabilities to achieve long-term sustainability. Conclusion: This study conceptualizes and measures entrepreneurial agility, confirming it as a key mediating factor in the relationship between entrepreneurial orientation and sustainable performance, thus contributing to Dynamic Capabilities Theory. The results provide useful implications for stakeholders, such as owners of micro, small, and medium enterprises, as well as policymakers, to strengthen entrepreneurship education and operational capabilities.